Gamification in Higher Education EFL: Integrating Duolingo and Kahoot to Enhance Motivation - Fauziah Tanjung; Masruddin; Jufriadi (Universitas Islam Negeri Palopo, 2026)
This study investigates the effect of gamification on the motivation of English as a Foreign Language (EFL) learners at UIN Palopo. Although previous studies have shown the benefits of gamification in language learning, limited research has explored the combined use of Duolingo and Kahoot among adult EFL learners in higher education. This study employed a quasi-experimental pretest-posttest control group design with a mixed-methods approach involving 34 second-semester accounting students divided into an experimental group and a control group. The experimental group received instruction through Duolingo and Kahoot, while the control group received conventional instruction. Data were collected using a 13-item motivation questionnaire and classroom observations. Quantitative data were analyzed using descriptive statistics and paired-samples t-tests, while qualitative data were analyzed through observation notes. The results revealed a significant improvement in students’ motivation in the experimental group, with mean scores increasing from 38.82 to 54.12 (t = -22.695, p < .001). Classroom observations also showed higher levels of engagement, participation, autonomy, and enthusiasm during gamified learning activities. These findings suggest that integrating Duolingo and Kahoot can effectively enhance EFL learners’ motivation and create a more engaging learning environment in higher education. Therefore, educators are encouraged to incorporate gamification strategies into EFL classrooms to support student motivation and active participation.